Sex at the interface: the origin and impact of sex differences in the developing human placenta - Amy E. Braun; Olivia R. Mitchel; Tania L. Gonzalez; Tianyanxin Sun; Amy E. Flowers; Margareta D. Pisarska; Virginia D. Winn (Biology of Sex Differences, 2022)
Highlights Placental sex differences exist from early prenatal development, and may help explain sex differences in pregnancy outcomes. Transcriptome profiling of early to mid-gestation placenta reveals that immune signaling is a hub of early prenatal sex differences. Differentially expressed genes between male and female placenta fall into the following functional associations: chromatin modification, transcription, splicing, translation, signal transduction, metabolic regulation, cell death and autophagy regulation, ubiquitination, cell adhesion and cell–cell interaction. Placental sex differences likely reflect the interaction of cell-intrinsic chromosome complement with extrinsic endocrine signals from the fetal compartment that accompany gonadal differentiation. Understanding the mechanisms behind sex differences in placental development and function will provide key insight into molecular targets that can be modulated to improve sex-biased obstetrical complications.